(untitled) (International Journal of Engineering and Computer Science, 2017)
Vibration control plays a very important role in the modern day world especially in control of earthquakes & in aerospace engineering. With reference to this, research is being carried out in this exciting field of smart intelligent structures. Control of vibrations in smart intelligent structures for a single input single output case using fast output sampling method is presented in this paper using the modeling done in Matlab-Simulink environment. The model is run & the simulation results are observed on the scopes. The simulation results show the effectiveness of the method presented in this paper, how the vibrations are suppressed in a shorter time.